Characterization of titanate nanotubes for energy applications. (August 2017) - Fernández-Werner, Luciana; Pignanelli, Fernando; Montenegro, Benjamín; Romero, Mariano; Pardo, Helena; Faccio, Ricardo; Mombrú, Álvaro W.
Graphical abstract: Highlights: Full structural characterization of H2 Ti3 O7 based nanotubes. X-ray Powder Diffraction refinement of titanium based nanostructures. Computational simulation of structural and vibrational properties. Abstract: In this work we present the synthesis and full structural characterization of hydrothermally synthesized titanate nanotubes (TNTs) for energy applications. It is of interest to characterize the building block of certain nanomaterials and their surface termination. This task is particularly difficult for nanotubes, where the exhibited surface curvature is a limitation for its study. We present the synthesis and thorough structural characterization through several experimental techniques for morphology and compositional characterization. Simulated X-rays powder diffraction patterns (XRPD) of real size nanotubes models are refined with experimental data. The building blocks for the TNT models were obtained from computational simulations by means of Density Functional Theory for H2 Ti2 O5 ·0.5H2 O, H2 Ti2 O5 ·H2 O, H2 Ti3 O7 and H2 Ti3 O7 ·0.67H2 O. Our procedure confirms that open‐ended TNTs are obtained, with ∼100 nm of length and 6(1) nm of inner diameter. By interpreting the XRPD data, the TNT building block was obtained and found to derive from H2 Ti3 O7, where the distance between [TiO6 ] octahedral layers is increased in accordance with H2 Ti3 O7 ·0.67H2 O. This model fully agrees with all the structural characterizations, validating this methodology and suggesting its potential use to study other nanomaterials.